γ-aminobutyric acid secreted from islet β-cells modulates exocrine secretion in rat pancreas - Park, Yong-Deuk (Baishideng Publishing Group Co., Limited, 2006)
AIM: To investigate the role of endogenous γ-amino-butyric acid (GABA) in pancreatic exocrine secretion. METHODS: The isolated, vascularly perfused rat pancreas was employed in this study to eliminate the possible influences of extrinsic nerves and hormones. Cholecystokinin (CCK; 10 pmol/L) was intra-arterially given to stimulate exocrine secretion of the pancreas. RESULTS: Glutamine, a major precursor of GABA, which was given intra-arterially at concentrations of 1, 4 and 10 mmol/L, dose-dependently elevated the CCK-stimulated secretions of fluid and amylase in the normal pancreas. Bicuculline (10 μmol/L), a GABA(A) receptor antagonist, blocked the enhancing effect of glutamine (4 mmol/L) on the CCK-stimulated exocrine secretions. Glutamine, at concentrations of 1, 4 and 10 mmol/L, dose-dependently increased the GABA concentration in portal effluent of the normal pancreas. The effects of glutamine on the CCK-stimulated exocrine secretion as well as the GABA secretion were markedly reduced in the streptozotocin-treated pancreas. CONCLUSION: GABA could be secreted from β-cells into the islet-acinar portal system after administration of glutainine, and could enhance the CCK-stimulated exocrine secretion through GABA(A) receptors. Thus, GABA in islet β-cells is a hormone modulating pancreatic exocrine secretion.